Numerical analysis of boundary layer flow and heat transfer over a shrinking cylinder - Najib, Najwa; Bachok, Norfifah (Semarak Ilmu Publishing, 2022)
The investigation concerning the movement of the viscous fluid and heat transfer rate when the cylinder shrinks is carried out. The role of curvature parameter and effect of cylinder parameter on skin friction and heat transfer rate were studied. The existence of a dual solution is observed and subsequently identifies which solution is stable. By using the similarity transformation, the boundary layer equations are transformed into nonlinear ordinary differential equations which are then solved numerically using bvp4c in MATLAB. The results for the skin friction coefficient, temperature gradient coefficient as well as velocity and temperature profiles are presented graphically. The effects of mass suction parameter and curvature parameter on flow and heat transfer characteristics are also presented. It is found that the dual solution existed when mass suction parameter greater or equal to 2. Cylinder surface diminished the performance of skin friction coefficient and heat transfer rate. The stability analysis result is performed to verify that the upper branch solution is stable and physically meaningful.